How Enhancing Immunity to Low‐Risk HPV Could Cure Recurrent Respiratory Papillomatosis. (15th March 2021) - Bai, Ke; Allen, Clint
Abstract : Recurrent respiratory papillomatosis (RRP) is currently treated with repeat surgical resection of papillomatous disease that does not address the fundamental underlying issue of chronic infection with low‐risk human papillomavirus. Here, we review the biology and immunology of low‐risk human papillomavirus (HPV) infections. Antiviral or antiangiogenic adjuvant treatments similarly address the papillomatous disease itself but do not activate HPV immunity. It is likely that only through immune‐mediated clearance of low‐risk HPV infection can patients with RRP be cured. In some patients, this occurs spontaneously. In others with more aggressive disease, adjuvant immunotherapy to activate immunity may be needed. Based on current understanding of antiviral immune responses, the only rational strategy to clear HPV‐infected epithelial cells is through activation of the T‐lymphocyte arm of the adaptive immune response. Translation of immunotherapies that are Food and Drug Administration‐approved or under clinical study for cancer, such as immune checkpoint blockade or engineered therapeutic vaccines, may provide a path toward tolerable and efficacious adjuvant immunotherapy for RRP. Level of Evidence: NA Laryngoscope, 131:2041–2047, 2021